A Novel Shear Reduction Insole Effect on the Thermal Response to Walking Stress, Balance, and Gait. (November 2014) - Wrobel, James S.; Ammanath, Peethambaran; Le, Tima; Luring, Christopher; Wensman, Jeffrey; Grewal, Gurtej S.; Najafi, Bijan; Pop-Busui, Rodica
Shear stresses have been implicated in the formation of diabetes-related foot ulcers. The aim of this study was to evaluate the effect of a novel shear-reducing insole on the thermal response to walking, balance, and gait. Twenty-seven diabetes peripheral neuropathy patients were enrolled and asked to take 200 steps in both intervention and standard insoles. Thermal foot images of the feet were taken at baseline (1) following a 5-minute temperature acclimatization and (2) after walking. Testing order was randomized, and a 5-minute washout period was used between testing each insole condition. Sudomotor function was also assessed. Gait and balance were measured under single and dual task conditions using a validated body worn sensor system. The mean age was 65.1 years, height was 67.3 inches, weight was 218 pounds, and body mass index was 33.9, 48% were female, and 82% had type 2 diabetes. After walking in both insole conditions, foot temperatures increased significantly in standard insoles. The intervention insole significantly reduced forefoot and midfoot temperature increases (64.1%, P = .008; 48%, P = .046) compared to standard insoles. There were significant negative correlations with sudomotor function and baseline temperatures ( r = .53-.57). The intervention demonstrated 10.4% less gait initiation double support time compared to standard insoles ( P = .05). There were no differences in static balance measures. We found significantly lower forefoot and midfoot temperature increases following walking with shear-reducing insoles compared to standard insoles. We also found improvements in gait. These findings merit future study for the prevention of foot ulcer.